Temporal Changes in Nucleus Morphology, Lamin A/C and Histone Methylation During Nanotopography-Induced Neuronal Differentiation of Stem Cells - Ankam, Soneela; Teo, Benjamin K. K.; Pohan, Grace; Ho, Shawn W. L.; Lim, Choon K.; Yim, Evelyn K. F. (Frontiers in Bioengineering and Biotechnology, 2018)
Stem cell differentiation can be regulated by biophysical cues such as nanotopography. It involves sensing and integration of these biophysical cues into their transcriptome with a mechanism that is yet to be discovered. In addition to the cytoskeletal and focal adhesion remodeling, nanotopography has also been shown to modulate nucleus morphology. Here, we studied the effect of nanotopography on the temporal changes in nuclei of human embryonic stem cells (hESCs) and human mesenchymal stem cells (hMSCs). Using a high throughput Multi-architecture (MARC) chip analysis, the circularity of the stem cell nuclei changed significantly on different patterns. Human ESCs and MSCs showed different temporal changes in nucleus morphology, lamin A/C expression and histone methylation during topography-induced neuronal differentiation. In hESCs, the expression of nuclear matrix protein, lamin A/C during neuronal differentiation of hESCs on PDMS samples were weakly detected in the first 7 days of differentiation. The histone 3 trimethylation on Lysine 9 (H3K9me3) decreased after differentiation initiated and showed temporal changes in their expression and organization during neuronal differentiation. In hMSCs, the expression of lamin A/C was significantly increased after the first 24 hours of cell culture. The quantitative analysis of histone methylation also showed a significant increase in hMSCs histone methylation on 250nm anisotropic nanogratings within the first 24 hours of seeding. This reiterates the importance of cell-substrate sensing within the first 24 hours for adult stem cells. The lamin A/C expression and histone methylation shows a correlation of epigenetic changes in early events of differentiation, giving an insight on how extracellular nanotopographical cues are transduced into nuclear biochemical signals. Collectively, these results provide more understanding into the nuclear regulation of the mechanotransduction of nanotopographical cues in stem cell differentiation.